Navigation in image-based Virtual Reality as the factor to elicit spatial presence experience - Mohd Muhaiyuddin, N.D. (Institute of Electrical and Electronics Engineers Inc., 2014)
Presence in Virtual Reality application can be defined as the user's feeling of being located in a synthetic environment. However, previous studies only produced results about the factors of Geometry-based Virtual Reality characteristics that could enhance user's presence experience. The studies on Image-based Virtual Reality is still lacking. Thus, we had conducted an exploratory study to find out the list of IBVR characteristics that could enhance user's spatial presence experience by using Repertory Grid technique. Based on our study, a few IBVR characteristics could enhance the experience. However, this paper only presents about overall navigation function in Image-based Virtual Reality as one of the factor that could enhance the experience. The result was analyzed with Focus Cluster Grid from WebGrid V. The features of the overall navigation should have standardized icon and ease of navigation. Â© 2014 IEEE.